Interpersonal relationship : professional communication skills for nurses - Arnold, Elizabeth; Boggs, Kathleen Underman (Saunders/Elsevier, 2011)
Acclaimed for its strong theoretical framework and consistent organization, Arnold and Boggs' Interpersonal Relationships: Professional Communication Skills for Nurses, 6th Edition, remains the definitive resource in developing effective communication with clients, families, and colleagues in order to achieve treatment goals in health care. This two-time AJN Book of the Year award-winner is thoroughly updated and includes current references describing how to modify communications strategies for various populations and situations including children, the elderly, end of life, health teaching, stress, crisis, and colleagues. Two new chapters address issues in contemporary health care related to promoting health safety and supporting continuity of care.Not only does this book present proven communications strategies and principles in nursing, psychology, and related theoretical frameworks, but also it challenges you to apply these strategies and principles to numerous exercises and practical nursing case studies. Written in terms of the nurse-client relationship, the cutting-edge communications strategies presented are key for nursing students and professional nurses. - Publisher